Food and Non-Food Consumption Patterns of Agricultural Migrant Households in Cilacap, Central Java, Indonesia - Kencana Anjani Puspa; Rubiyanto Cahyo Wisnu; Widadie Fanny (BIO Web of Conferences)
Food stands as the cornerstone of human existence, serving as the quintessential necessity for sustaining life, especially for those people who living outside as migrant worker. This research aims to explore the food and non-food consumption patterns of Agriculture Migrant Household. This study was conducted on August 2023. The sampling method was purposive sampling in Binangun and Nusawungu sub-districts, Cilacap District, Central Java Province. Considering that according to BP2MI 2023 data, Cilacap Regency is the third-largest contributor of Indonesian migrant workers and has the highest number of PMI (Indonesian Migrant Workers) in Central Java. The average expenditure for migrant households is higher (IDR 13,254,783) than non-migrant households (IDR 12,348,120). Migrant households show significantly higher expenditures on food and non-food items, primarily driven by remittances that enhance their economic stability, allowing for better health and education investments. The migrant households benefit economically from remittances, non-migrant households display a more constrained expenditure pattern, often aligning closely with their limited income levels. This disparity underscores the critical role that migration plays in shaping economic behaviours and consumption decisions within communities.